Convention of Generations in the New World of Education - A. A. Fedorov; E. Yu. Ilaltdinova; S. V. Frolova (Высшее образование в России, 2018)
The article addresses the issues of intergenerational interaction of subjects of educational space in conditions of the modern changing world. The authors propose and substantiate a conventional approach to determine the nature of interaction between a Teacher and a Student. An empirical basis for developing this approach was an analysis of the theories of generations and the age structure of the pedagogical community of the Russian Federation. The study presents statistical data on the characteristics of the age structure of the pedagogical community at the federal, regional and institutional levels. The specifics of the perception by the teachers and students of the role of modern student youth in the life of the university, the difference in value orientations in the changing world of education are indicated. The authors emphasize the significance of the problem posed by the interaction of generations in the educational organization. The fundamental principle of interaction between the Student and the Teacher within the framework of the conventional approach viewed as a new methodological approach is the principle of the convention of generations. This approach is presented in comparison with the existing modern approaches to the organization of interaction between the subjects of educational space (event, subject-subject, environmental) as a new conceptual framework that defines the goals, principles, methods and results of the interaction between all subjects of the educational space. These subjects are considered as representatives of different but equal generations in the context of the space of continuous education of each of them, the result of which is cooperative educational effect achievement. The article dwells on the characteristics of the “convention of generations” as a multi-vector interaction of generations that overcomes the shortcomings of one-way interaction of generations as a transfer of experience and knowledge from older to younger. The one-way interaction strategy forms the so-called “presumption of incompetence” of the younger generation that generates excessive custody that goes to the authoritarianism and does not promote the development of such qualities in the younger generation as independence, responsibility, initiative, creativity.